SECULAR OR POST SECULAR? Korea as a Multi-Religious Society - Lee, Young-Jun (Journal of Dharma, 2019)
Despite predictions that modernization would threaten the existence of religion, Korean religions have thrived throughout the process of modernization. Unlike many Western countries, where Christianity is the principal religion, multiple religions and beliefs have co-existed in Korea since antiquity. Thus, even if social change brings the downfall of one religion, another religion takes its place. Although Korea has never historically seen the decline of religion, a decrease in the religious population has been observed since 2010. We believe this is attributable to the secularization of institutional religions and could be interpreted as another choice or change in itself, rather than as evidence of the decline or deterioration of religiosity. We argue that Korean religions are going through the post-secularization process, wherein people seek out their own individual spirituality. Based on Western theories of secularization and post-secularization, we examine the changes in Korean religious diversity, and discuss the challenges they face. This will, finally, lead to helping reveal what Korean religious institutions have to do for Koreans to find their way into religion again.